JPE Turnaround Times, Previous Two Years (Journal of Political Economy, 2020)
Previous article FreeJPE Turnaround Times, Previous Two YearsFull TextPDF Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJPE Turnaround Times, Previous Two Years Outcome of 1st Round DecisionsMean Days to DecisionMedian Days to DecisionDecision Later than Six Months after Submission (as percentage of decisions within decision type)Desk Rejection49%1070%Reject with Reviews44%11810013%Revise7%16915938%Average time from original submission to acceptance (omitting time with author in revision) = 431 days View Table Image Previous article DetailsFiguresReferencesCited by Journal of Political Economy Volume 128, Number 8August 2020 Article DOIhttps://doi.org/10.1086/710656 Views: 314 © 2020 by The University of Chicago. All rights reserved. Crossref reports no articles citing this article.